2017
DOI: 10.1083/jcb.201608002
|View full text |Cite
|
Sign up to set email alerts
|

Osteoblastic Lrp4 promotes osteoclastogenesis by regulating ATP release and adenosine-A2AR signaling

Abstract: Lrp4 is mutated in patients with high-bone-mass diseases. Loss of Lrp4 in osteoblasts (OBs) increases bone formation by OBs and decreases bone resorption by osteoclasts through an unclear mechanism. Xiong et al. show that overproduction of extracellular adenosine in Lrp4-deficient OBs, which are derived from ATP hydrolysis and signals through A2AR and RANK, may underlie Lrp4 regulation of osteoclastogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 80 publications
0
16
0
Order By: Relevance
“…The V-ATPase resides within many intracellular compartments such as endosomes, lysosomes and secretory vesicles, which are crucial for maintaining the intracellular vesicular acidic environment [63]. PRR ablation in cultured cells results in the downregulation of several subunits of the V0 complex of the V-ATPase and impairs vesicle acidification [44,62,64,65]. BACE1 activity is optimal in acidic environments [17,18,19].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The V-ATPase resides within many intracellular compartments such as endosomes, lysosomes and secretory vesicles, which are crucial for maintaining the intracellular vesicular acidic environment [63]. PRR ablation in cultured cells results in the downregulation of several subunits of the V0 complex of the V-ATPase and impairs vesicle acidification [44,62,64,65]. BACE1 activity is optimal in acidic environments [17,18,19].…”
Section: Resultsmentioning
confidence: 99%
“…We then examined BACE1 activity between control and PRR-KD (knockdown) cells. PRR was knocked down by infection of MC3T3 cells (an osteoblastic cell line that expresses PRR, APP and BACE1) with shRNA-PRR lentivirus [44,66] (Figure 8E). Aβ (1–40) levels were measured by ELISA and used to represent BACE1 activity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated osteoclast activity reduces the bone volume and degrades bone to the primary bone state [ 20 ]. Some scholars demonstrated that A2AR inhibits both osteoclast formation and function [ 20 , 23 , 24 ]. The MAPK signaling pathway is also important in A2AR regulation of osteoclasts.…”
Section: Discussionmentioning
confidence: 99%
“…For example, human osteoblasts expressed low-density lipoprotein receptorrelated protein (LRP) 1 with a capacity for osteocalcin carboxylation (28). LRP4, LRP5/6, and LRP8 were involved in the maintenance of bone (29)(30)(31)(32)(33)(34)(35)(36). However, the role of LDLR in bone metabolism was unclear with controversial results in recent studies.…”
Section: Introductionmentioning
confidence: 99%